Amino Acid Compositions of 27 Food Fishes and Their Importance in Clinical Nutrition. (14th October 2014) - Mohanty, Bimal; Mahanty, Arabinda; Ganguly, Satabdi; Sankar, T. V.; Chakraborty, Kajal; Rangasamy, Anandan; Paul, Baidyanath; Sarma, Debajit; Mathew, Suseela; Asha, Kurukkan Kunnath; Behera, Bijay; Aftabuddin, Md.; et al.
Abstract : Proteins and amino acids are important biomolecules which regulate key metabolic pathways and serve as precursors for synthesis of biologically important substances; moreover, amino acids are building blocks of proteins. Fish is an important dietary source of quality animal proteins and amino acids and play important role in human nutrition. In the present investigation, crude protein content and amino acid compositions of important food fishes from different habitats have been studied. Crude protein content was determined by Kjeldahl method and amino acid composition was analyzed by high performance liquid chromatography and information on 27 food fishes was generated. The analysis showed that the cold water species are rich in lysine and aspartic acid, marine fishes in leucine, small indigenous fishes in histidine, and the carps and catfishes in glutamic acid and glycine. The enriched nutrition knowledge base would enhance the utility of fish as a source of quality animal proteins and amino acids and aid in their inclusion in dietary counseling and patient guidance for specific nutritional needs.